2008
DOI: 10.1007/s00436-008-1173-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Azadirachta indica extracts against Boophilus microplus

Abstract: Extracts were prepared from leaf, bark, and seed of Azadirachta indica, leaf and seed of Prunus persica, bark of Mangifera indica, and leaf of Psidium guajava and were evaluated against Boophilus microplus. Of the eight extracts screened, the extracts prepared from the A. indica seed showed very high level of efficacy (80%) after 5 h of treatment. Besides the immediate effect on adult ticks, the egg-laying properties of the survived ticks was also assessed, and a significant reduction (P < 0.01) in the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 9 publications
5
35
0
4
Order By: Relevance
“…(B.) microplus (SRIVASTAVA et al, 2008;MAGADUM et al, 2009). The biochemical effects of this extract over the cattle tick remains unclear, but Habluetzel et al (2007) found that the extract produced a reduction in the survival of the larvae and adults and also interfered with oviposition and oogenesis, behavior, dietary process, and growth of arthropods (SCHMUTTERER, 1990;MORDUE;NISBET, 2000;BROGLIO-MICHELETTI et al, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…(B.) microplus (SRIVASTAVA et al, 2008;MAGADUM et al, 2009). The biochemical effects of this extract over the cattle tick remains unclear, but Habluetzel et al (2007) found that the extract produced a reduction in the survival of the larvae and adults and also interfered with oviposition and oogenesis, behavior, dietary process, and growth of arthropods (SCHMUTTERER, 1990;MORDUE;NISBET, 2000;BROGLIO-MICHELETTI et al, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…caniculi) (Sarcoptes scabies varovis) [54,55] and ticks (Boophilus microplus) [56]. The pesticide activity of this fixed oil is generally thought to be due to azadirachtin, which is a well-known potent insecticide [57].…”
Section: Discussionmentioning
confidence: 99%
“…The Eucalyptus globules essential oils at 5.0 % concentration produced 37.5 % mortality after six days post treatment in adult stage of R. (B) microplus with Pongamia glabra extract and seed oil resulted in lower egg production and hatchability (Bisen et al 2010(Bisen et al , 2011, neem seed oil/extracts (Azadirachta indica) elicited acaricidal effects on egg, immature, and adult stages of Hyalomma anatolicum excavatum (AbdelShafy and Zayed 2002) and R.(B.) microplus (Srivastava et al 2008). Different species from the genus Tephrosia were studied for larvicidal, insecticidal, and antifeedant activities.…”
Section: Discussionmentioning
confidence: 99%